FOSTERING CRITICAL THINKING IN BIVARIATE DATA ANALYSIS INSTRUCTION FOR SENIOR HIGH SCHOOL TEACHERS IN NGANJUK REGENCY - Adawiyah, Rabiatul; Anuraga, Gangga; Sadewa, Arief Triatmaja Permana (Universitas Muhammadiyah Lamongan, 2025)
Statistics education is a vital component of the learning process, particularly in fostering logical, analytical, and quantitative thinking skills. Within this context, critical thinking plays a crucial role. Critical thinking is defined as the ability to objectively analyze information, evaluate arguments, identify assumptions, and draw logical conclusions. The development of critical thinking skills in statistics education aligns closely with the demands of the 21st century. This seminar aims to positively impact educators and students, specifically high school teachers in Nganjuk Regency, through the subtopic